2018
DOI: 10.1590/fst.32916
|View full text |Cite
|
Sign up to set email alerts
|

Storage stability of sweet biscuit elaborated with recovered potato starch from effluent of fries industry

Abstract: The effluent from the potato chips processing could be recovered and used in the biscuit formulations. This study aimed to evaluate the changes of sweet biscuits with partial replacement (45%) of wheat flour by recovered potato starch, packed in biaxial oriented polypropylene (BDPP), and stored under two controlled temperatures (25°C and 35°C). The changes of physical, chemical, microbiological and sensory characteristics of biscuits were evaluated for 6 months. Completely randomized design with 2x6 factorial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 14 publications
6
5
0
Order By: Relevance
“…Our results are in line with the study of Morais et al. (2018). Interestingly, although microbial count was increased gradually within the studied period but it was still in range.…”
Section: Resultssupporting
confidence: 94%
“…Our results are in line with the study of Morais et al. (2018). Interestingly, although microbial count was increased gradually within the studied period but it was still in range.…”
Section: Resultssupporting
confidence: 94%
“…Although water activity increased after fourth week of storage and this remained constant up to 8 weeks. Morais et al (2018) also reported a similar behavior of storage changes in biscuits samples. The increased water activity can be attributed to the increased moisture of biscuits with respect to storage.…”
Section: Resultsmentioning
confidence: 56%
“…Hardly any moisture change was observed in soft cookies during storage yet firming and grainess, which are an indication of quality reduction, occurred as a result of sucrose recrystallization within the cookie [16]. In another study, no increase in Aw was reported for the first 36 days and thereafter remaining constant up to 144days of storage of sweet biscuits from wheat flour/potato starch, however, biscuit hardness increased with attendant reduction in texture sensory scores, probably as a result of starch retrogradation facilitated by increased moisture in the biscuit [17].…”
Section: Resultsmentioning
confidence: 99%